Absorption Spectra for Firefly Bioluminescence Substrate Analog: TokeOni in Various pH Solutions. (21st June 2021) - Ogawa, Haruhisa; Ono, Ryohei; Noguchi, Yoshifumi; Kitada, Nobuo; Saito‐Moriya, Ryohei; Maki, Shojiro A.; Akiyama, Hidefumi; Itabashi, Hideyuki; Hiyama, Miyabi
Abstract: AkaLumine hydrochloride, named TokeOni, is one of the firefly luciferin analogs, and its reaction with firefly luciferase produces near‐infrared (NIR) bioluminescence. Prior to studying the bioluminescence mechanism, basic knowledge about the chemical structures, electronic states, and absorption properties of TokeOni at various pH values of solution has to be acquired. In this paper, the absorption spectra for TokeOni and AkaLumine at pH 2–10 were measured. Density functional theory (DFT) calculations, time‐dependent DFT calculations, and the vibrational analyses were carried out. The absorption spectra indicate that the chemical forms of TokeOni in solutions are same as those of AkaLumine. The peaks at pH 7–10 in the absorption spectra correspond to the excitation from the ground state of a carboxylate anion of AkaLumine, the peak at pH 2 corresponds to the excitation from the ground state of a carboxylate anion with an N‐protonated thiazoline ring and N‐protonated dimethylamino group of AkaLumine, and the peak at pH 4 corresponds to the excitation from the ground state of a carboxylate anion with an N‐protonated thiazoline ring of AkaLumine. Abstract : The absorption spectra of AkaLumine and its hydrochloride, named TokeOni, were measured at various pH values. The absorption spectra indicate that the chemical forms of TokeOni in solutions are the same as those of AkaLumine. The peaks at pH 7–10, pH 4, and pH 2 of AkaLumine are assigned to a carboxylate anion, a carboxylate anion with an N‐protonated thiazoline ring, and a carboxylate anion with an N‐protonated thiazoline ring and N‐protonated dimethylamino group, respectively.